Life history, distribution and molecular phylogenetics of the Upward‐Mouth Spikefish Atrophacanthus japonicus (Teleostei: Tetraodontiformes: Triacanthodidae). Issue 4 (21st March 2019) - Bemis, Katherine E.; Tyler, James C.; Arcila, Dahiana
Abstract : Ninety‐six juvenile specimens (37–54 mm standard length; L S ) of the rarely collected Upward‐Mouth Spikefish Atrophacanthus japonicus (Triacanthodidae) were obtained from the stomachs of three Yellowfin Tuna Thunnus albacares collected off Guam in the Mariana Islands in the central Pacific Ocean. These specimens extend the range of A. japonicus eastward into Oceania. We review the systematic characters of the monotypic genus Atrophacanthus and present colour photographs of freshly collected specimens. The diet of the juvenile specimens of A. japonicus consisted of thecosome pteropods and foraminiferans. We present a range map of A. japonicus based on all known specimens and show that specimen size is related to whether specimens were collected in the pelagic zone or on the bottom. Our results support that, compared to all other Triacanthodidae, A. japonicus has an unusually extended pelagic larval and juvenile period, up to 54 mm L S, before settling to the bottom as adults. Lastly, we provide a multilocus phylogeny addressing the phylogenetic placement of Atrophacanthus based on eight of 11 triacanthodid genera and six genetic markers. Our results reveal that Atrophacanthus is the sister group of Macrorhamphosodes and they provide new insights about the evolutionary history of the family.